2006
DOI: 10.1146/annurev.matsci.36.020105.104035
|View full text |Cite
|
Sign up to set email alerts
|

Structural Order in Liquids Induced by Interfaces With Crystals

Abstract: ▪ Abstract  Interfaces between solids and liquids are important for a range of materials processes, including soldering and brazing, liquid-phase sintering, crystal growth, and lubrication. There is a wealth of fundamental studies on solid-liquid interfaces in materials, primarily focused on thermodynamics (relative interface energies and segregation effects) from high-temperature wetting experiments, which is often applied to processing design. Less is known about the atomistic structure at solid-liquid inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(113 citation statements)
references
References 137 publications
5
108
0
Order By: Relevance
“…Metals form a wide variety of interfaces, including grain and phase boundaries [1], surface-liquid interfaces [2,3], solidification fronts [4], and mechanical contacts [5]. Although they typically occupy a small fraction of the total volume, interfaces play an outsized role in determining the properties of metals [6][7][8][9].…”
Section: Interfaces In Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metals form a wide variety of interfaces, including grain and phase boundaries [1], surface-liquid interfaces [2,3], solidification fronts [4], and mechanical contacts [5]. Although they typically occupy a small fraction of the total volume, interfaces play an outsized role in determining the properties of metals [6][7][8][9].…”
Section: Interfaces In Metalsmentioning
confidence: 99%
“…Low energy neutrons are typically detected indirectly through absorption reactions with materials of high cross-sections for such reactions. Typically, 3 He, 6 Li, or 10 B is used to emit high-energy particles, whose ionization signatures may be detected by a number of means.…”
Section: Interfaces In Metalsmentioning
confidence: 99%
“…The feed throughs are using a teflon plug to seal in the pressure. Additionally, there are four multi connectors of which one is reserved for a safety valve, marked (2), which opens at 50 bar. The others, marked (3), can be used for gas lines and a pressure gauge.…”
Section: The Chambermentioning
confidence: 99%
“…The 'buried' interfaces between two bulk systems, as described above, are often causing interesting phenomena. Examples are enhanced liquid density [1], liquid order [2] or liquid layering [1,3,4]. These phenomena are important factors with respect to the mass transport towards the growing interface and therefore growth speed and crystalline quality.…”
Section: Introductionmentioning
confidence: 99%
“…An in situ study of an alumina-aluminum interface using a high-resolution transmission electron microscope provides experimental evidence of ordering of the liquid molecules at a Kaplan and Kauffmann [63] reviewed both theoretical and experimental studies of liquid molecule ordering adjacent to crystalline solids. Gerardi et al [64] observed layering of water (forming a ~1.4 nm thick layer) on alumina particles using NMR, but they did not measure an anomalous conductivity enhancement.…”
Section: 1 1 T H E R M a L C O N D U C T I V I T Ymentioning
confidence: 99%